Exploring the Moderating Effect of Interpersonal Emotion Regulation Between the Integration of Opportunity and Resource and Entrepreneurial Performance - Li, Na; Sun, Yu; Jiang, Dake; Yang, Xiu (Frontiers in Psychology, 2021)
This study explains how start-ups obtain a high accumulated performance by aligning and employing an integration between opportunities and resources (IOR) in a dynamic environment and whether these potential benefits are associated with interpersonal emotion regulation. Using 274 enterprise samples, the findings confirm that an IOR has a significant positive effect on entrepreneurial performance. In addition, positive emotion and interpersonal relationship regulation positively moderate the relationship between IOR and entrepreneurial performance. This paper proposes a new concept of the IOR and measures it for the first time. Then, the relationship was explored between the IOR, interpersonal emotion regulation, and entrepreneurial performance. This research not only systematically integrates opportunities and resources and avoids their separation but also helps to reveal the context of entrepreneurship research, enrich entrepreneurship theory, and expand the boundaries.